Time‐series high‐resolution spectroscopy and photometry of ε Aurigae from 2006–2013: Another brick in the wall1. Issue 9 (November 2014) - Strassmeier, K. G.; Weber, M.; Granzer, T.; Schanne, L.; Bartus, J.; Ilyin, I.
Abstract We present continuous and time‐resolved R = 55 000 optical échelle spectroscopy of ε Aurigae from 2006–2013. Data were taken with the STELLA Echelle Spectrograph of the robotic STELLA facility at the Observatorio del Teide in Tenerife. Contemporaneous photometry with the Automatic Photoelectric Telescopes at Fairborn Observatory in Arizona is presented for the years 1996–2013. Spectroscopic observations started three years prior to the photometric eclipse and are still ongoing. A total of 474 high‐resolution échelle spectra are analyzed and made available in this paper. We identify 368 absorption lines of which 161 lines show the characteristic sharp disk lines during eclipse. Another 207 spectral lines appeared nearly unaffected by the eclipse. From spectrum synthesis, we obtained the supergiant atmospheric parameters Teff = 7395 ± 70 K, log g ≈ 1, and [Fe/H] = +0.02 ± 0.2 with ξt = 9 km s–1, ζRT = 13 km s–1, and v sin i = 28 ± 3 km s–1. The residual average line broadening expressed in km s–1 varies with a period of 62.6 ± 0.7 d, in particular at egress and after the eclipse. Two‐dimensional line‐profile periodograms show several periods, the strongest with ≈110 d evident in optically thin lines as well as in the Balmer lines. Center‐of‐intensity weighted radial velocities of individual spectral lines also show the 110‐d period but, again, additional shorter and longer periods are evident and are different in the Balmer lines. The two main spectroscopic Hα periods, ≈ 116 d from the line core and ≈ 150 d from the center‐of‐intensity radial velocities, appear at 102 d and 139 d in the photometry. The Hβ and Johnson V I photometry on the other hand shows two well‐defined and phase‐coherent periods of 77 d and 132 d. We conclude that Hα is contaminated by changes in the circumstellar environment while the Hβ and V I photometry stems predominantly from the non radial pulsations of the F0 supergiant. We isolate the disk‐rotation profile from 61 absorption lines and found that low disk eccentricity generally relates to low disk rotational velocity (but not always) while high disk eccentricity always relates to high velocity. There is also the general trend that the disk‐absorption in spectral lines with higher excitation potential comes from disk regions with higher eccentricity and thus also with higher rotational velocity. The dependency on transition probability is more complex and shows a bi‐modal trend. The outskirts of the disk is distributed asymmetrically around the disk and appears to have been built up mostly in a tail along the orbit behind the secondary. Our data show that this tail continues to eclipse the F0 Iab primary star even two years after the end of the photometric eclipse. High‐resolution spectra were also taken of the other, bona‐fide, visual‐binary components of ε Aur (ADS 3605BCDE). Only the C‐component, a K3‐4‐giant, appears at the same distance than ε Aur but its radial velocity is in disagreement with a bound orbit. The other components are a nearby (≈ 7 pc) cool DA white dwarf, a G8 dwarf, and a B9 supergiant, and not related to ε Aur. The cool white dwarf shows strong DIB lines that suggest the existence of a debris disk around this star. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)